DOMESTIC VIOLENCE IN THE CONTEXT OF THE COVID-19 PANDEMIC (VERUM: Journal of Scientific Initiation, 2022)
This academic article was designed with the purpose of examining the impacts of the COVID-19 pandemic on cases of domestic and family violence. The outbreak, which culminated in social isolation, trapped women in an unbalanced environment, which, due to several biopsychosocial factors, became conducive to aggression against them. Additionally, it aimed to identify the main challenges and difficulties historically faced by women in ensuring their fundamental rights and the creation of laws aimed at protecting women from violence. Regarding methodology, this article is based on a literature and documentary review, with a qualitative approach. It involved studying results already published in articles and academic journals, found on Google Scholar and Scielo platforms, as well as data from public security agencies. In this regard, after analyzing research and publications on the topic, it can be concluded that the results presented by the main public security agencies do not accurately reflect the rates of domestic violence during the pandemic. This is because isolation made it more difficult to report cases due to the constant surveillance of the abusers, who spent more time with the victims due to the imposed isolation.
Keywords: Pandemic; COVID-19; Domestic and Family Violence